Strengthening health sector capacities through permanent health education: workshops addressing public health emergencies in Brazil - Almeida, Taynná Vernalha Rocha; Schelle, Danielly Portes; Costa, Paula Orofino Moura; Miquilin, Isabella de Oliveira Campos; Santos, Caroline Martins José dos; de Oliveira, Paola Freitas; Castro, Joelma Ferreira Gomes; Moreira, Leonora Rios de Souza; Inoue, Vinicius Chozo; Filho, Edenilo Baltazar Barreira; Garcia, Márcio Henrique de Oliveira (Frontiers in Public Health, 2025)
This initiative strengthens Brazil's Unified Health System (SUS) by enhancing preparedness, public health surveillance, and response capacities to public health emergencies across 27 Federative Units (FUs). Employing andragogical active methodologies, 156 action plans were developed, addressing preparedness (34.7%), public health surveillance (31.8%), and response (33.5%). Training in small groups fostered situational analyses, collaborative planning, and practical application of theoretical knowledge, creating a scalable and replicable model for nationwide implementation.